MAXIMUM EQUILIBRIUM YIELDS OF DEMERSAL FISHERIES BASED ON EXPLORATORY TRAWLING - Krishnamurthy, B (Indian Journal of Fisheries, 2011)
In most of the groups of fishes exploited in the 17Â° 40' zone along theAndhra-Orissa coast the maximum equillibrium yields are not far different from the average yields. Hence the stock in this zone can but stand in future only a limited increase in fishing pressure.